2008
DOI: 10.1007/s10517-009-0403-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transformations of Myocytes during Gestation and Early Postpartum Involution of the Uterus

Abstract: Myocytes with large homogeneous vacuoles and numerous protrusions of the cytoplasm into extracellular space (manifestations of clasmatosis) were detected in rat myometrium during normal gestation and early postpartum period. The percentage of vacuolated smooth-muscle cells and numerical density of inflammatory cells in the myometrium were evaluated. The data indicate the absence of typical inflammatory reaction in the myometrium during elimination of smooth-muscle cells in the course of postpartum involution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The size of both myocytes and their nuclei decreased compared to the corresponding values in intact mice ( Table 2). At the same time, myocytes referred by us to types 3 and 4 [4] (in the state of vacuolar and balloon degeneration) and sometimes necrotic myocytes were found during the involution period in multigravida mice. The relative counts of type 3 and 4 myocytes in the myometrium were maximum before delivery and were similar in primigravida and multigravida mice.…”
Section: Notementioning
confidence: 84%
See 3 more Smart Citations
“…The size of both myocytes and their nuclei decreased compared to the corresponding values in intact mice ( Table 2). At the same time, myocytes referred by us to types 3 and 4 [4] (in the state of vacuolar and balloon degeneration) and sometimes necrotic myocytes were found during the involution period in multigravida mice. The relative counts of type 3 and 4 myocytes in the myometrium were maximum before delivery and were similar in primigravida and multigravida mice.…”
Section: Notementioning
confidence: 84%
“…The preparations were morphometried at ×400 using a closed test system consisting of 25 squares with an area of 1600 μ 2 . We measured volume densities (Vv) of myocyte nuclei and cytoplasm, myometrium and its vessels, collagen fi bers in the myometrium stroma, and myocytes in the state of vacuolar (type 3) and balloon (type 4) degeneration [4]. Moreover, numerical densities (Nai) of myocytes, their nuclei, and perpendicular and tangential profi les of blood vessels were evaluated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Postpartum involution of the uterus involves all its structures: the endometrium [4] and myometrium [5,6] with involvement of the myometrial interstitium components: collagen and vessels [3]. It was shown that during 5 days of the involution period after the fi rst pregnancy rats develop myocyte necrosis and apoptosis, autophagocytosis and clasmocytosis of their cytoplasm; each of these processes can be regarded as a mechanism of physical and functional elimination of myometrial structures "excessive" for that period [5,6].…”
mentioning
confidence: 99%